Assessment of pollution and other impairments of US reservoirs based on expert opinion - Miranda, L. E.; Shoemaker, D. J.; Krogman, R. M. (Frontiers in Environmental Science, 2024)
A comprehensive understanding of the prevalent pollution and other impairments in reservoirs is necessary nationally to analyze patterns and causes, and allocate national resources effectively.Many of these impairments are associated with sedimentation, nutrient contamination, and other pollution factors. The costs involved in performing on-site surveys of multiple locations are a potential obstacle in obtaining empirical data on impairment at a large spatial extent. In this case, input from specialists may be required to tackle the absence of empirical data that are required to determine the impairment status of thousands of geographically dispersed reservoirs. Our aim was to examine whether expert opinion could offer a comprehensive review of the impairment status of numerous reservoirs in the conterminous United States. We designed and executed an internet-based survey of reservoir specialists to gather their ratings of visually evident elements of reservoir impairment. To evaluate the ratings, we searched for correlations with factors known to have an impact on reservoir impairment. Canonical correlation analyses indicated that nine metrics, which were used by experts to rate impairment levels in an ordinal scale, were correlated with metrics descriptive of physical qualities of the reservoirs, land use in catchments, and the prevailing local climate. We conclude that expert opinion may facilitate assessment of impairment levels over large geographic areas. Lastly, we define the circumstances under which it is permissible to rely on expert opinion and propose criteria that may improve the quality of the data collected.